Pegiat Perdamaian: Dari Ideologi Menuju Visi Politik - Semy Arayunedya (Societas Dei: Jurnal Agama dan Masyarakat, 2025)
The study of peace and religion cannot be separated from the study of politics because most of us live in countries or political communities, namely, communities that bind citizens and governments, which at least aim to uphold and maintain justice. In other words, peace activists will be involved in politics, both at the operational and ideological levels. The former leads to public policy. Mapping actors and their relationships is a valuable skill for activists as an advanced skill. Afterward, ideology is absolutely essential to study because it is what gives rise to policies that promote peace or, conversely, violence.